Value of pacing in cardiac failure associated with chronic atrioventricular block. Issue 8 (August 1978) - Hetzel, M R; Ginks, W R; Pickersgill, A J; Leatham, A
Abstract : The effect of permanent pacing on chronic complete atrioventricular block complicated by cardiac failure was studied in 6 patients by measurement of indirect left atrial pressure 15 minutes after institution of pacing and again 3 to 12 months later. In addition, 21 patients with complete heart block and clinical plus radiological evidence of cardiac failure at the time of pacing 3 to 6 years earlier were also reviewed. Only 1 of 6 patients studied haemodynamically improved and 1 died in cardiac failure. Of 21 patients assessed clinically, 10 had improved and 8 had died after a mean follow-up of 53 months. In the absence of syncope, pacing was of little symptomatic benefit but still may be justified to prolong survival. Both studies indicated a particularly poor prognosis for patients known to have coronary artery disease. No reliable means were found of determining the prognosis in the individual patient with cardiac failure before pacing.